UPAYA MENINGKATKAN KOMPETENSI GURU MAPEL IPA DALAM MENERAPKAN MODEL PEMBELAJARAN DAN PENGELOLAAN KELAS MELALUI PEMBIMBINGAN KEPALA SEKOLAH DI SMP NEGERI 1 NGEMPLAK SEMESTER 2 TAHUN PEMBELAJARAN 2013/2014 - -, Suwarto (Widya Wacana: Jurnal Ilmiah, 2014)
This study was conducted to determine the competence of teachers in applying the model of learning and classroom management in the classroom is more appropriate to the subject by the teacher IPA SMP Negeri 1 Ngemplak Semester 2, in 2013/2014 school year This study was conducted to the subject teacher IPA SMP Negeri1 Ngemplak Boyolali, Central Java province in Semester 2, 2013/2014 school year. Samples taken areall subject teachers science as a subject of research with action throughearly action, actioncycle If ollowed the second cycle. The method used in this research is Action Research School. The collection of data for the application of competence learning model and classroom management are observed at the beginning of the action, the actionfirst cycle, and the second cycle. Collecting data for observations guiding principals activity throughpeer observation one arly action, action first cycle, and the second cycle. Hypothes is test result sobtained from subject teachers IPA SMP Negeri 1 Ngemplak Semester 2, in 2013/2014 school year. that: Competence maple science teachers has Â increased to: 1) Competencelearning model for the application of the criteria verywell: froma number of 0 or 0% on prasiklus in creased to 2 or 33.33% in the first cycleandincreased to 3 or 50% in the second cycle. Both criteria: froma number 2 or 33.33% on prasiklus increased to 4 or 66.67% in the first cycleandreduced to 3 or 50% in cycle 2. Criteria Enough: from number1 or 16.67% on prasiklus reduced to 0 or 0% on cycle I and reducedagain to 0 or 0 % in the second cycle. CriteriaLess: from number 3 or 50% on prasiklus reduced to 0 or 0% in the first cycleandreducedaga into 0 or 0% in the second cycle 2) Classroom Management Competence: tocriteria very well: froma number of0or0% onprasiklusincreased to2or33.33% in the first cycleandincreased to3or50% in the second cycle. Both criteria: a number1or16.67% on prasiklusincreased to 4 or 66.67% in the first cycleandreduced to 3 or 50% in the second cycle. Quitecriteria: froma number 2 or 33.33% on prasiklusreduced to 0 or 0% in the first cycleandreducedaga into 0 or 0% in the second cycle. CriteriaLess: from number 3 or 50% on prasiklusreduced to 0 or 0% in the first cycleandreducedaga into 0 or 0% in the second cycle Â  Kata Kunci: Kompetensi guru, Model Pembelajaran, Pengelolaan Kelas, Kreatifitas mengajar, Mapel IPA, Profesionalisme Guru.